FAKTOR-FAKTOR YANG MEMPENGARUHI OPINI AUDIT BPK ATAS LKPD PROVINSI NUSA TENGGARA TIMUR ( TAHUN 2024-2025) - Baso, Susana P; Loinenak, Jeanet J.S; Semi, Yohanes E; Bolla, Larasati V; Kabba, Melkianus N (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2025)
This study aims to examine the factors influencing the audit opinion of the Supreme Audit Agency (BPK) on Regional Government Financial Reports (LKPD) in East Nusa Tenggara Province in 2024-2025. The method used is a descriptive qualitative approach, by collecting data through document studies of LKPD and BPK Audit Reports (LHP), in-depth interviews with employees who manage regional finances and auditors, and indirect observation. The data analysis process was carried out using the Miles and Huberman model, which includes three stages: data reduction, data presentation, and conclusion drawing.The research results indicate that the Supreme Audit Agency (BPK)'s audit opinion on the Regional Financial Report (LKPD) of East Nusa Tenggara Province is influenced by several key factors, namely the quality of financial report presentation in accordance with Government Accounting Standards (SAP), the effectiveness of the internal control system, the level of compliance with laws and regulations, and the ability of human resources to manage regional finances.The 2024 BPK audit results revealed weaknesses in asset management, the internal control system, and regulatory compliance. However, improvements gradually emerged in 2025 due to follow-up on BPK recommendations, enhanced internal oversight, and increased capacity of regional financial officials. This study concludes that the BPK's audit opinion not only reflects whether the financial statements are presented fairly for a given period but also reflects the results of ongoing efforts to improve regional financial management.